2019
DOI: 10.3389/fpsyg.2019.00327
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and In-Service Teachers’ Attitudes Toward Students With Learning Difficulties and Challenging Behavior

Abstract: The implementation of inclusive policies is largely dependent on teachers’ willingness to accommodate students with special educational needs (SEN) in mainstream classrooms, which is affected by their perceived competence and attitudes. This study investigated attitudes of pre- and in-service teachers toward students with two types of SEN: challenging behavior and learning difficulties. The three components of attitudes (affective, cognitive, and behavioral) were assessed using indirect and direct measures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 66 publications
0
29
0
9
Order By: Relevance
“…In addition, intergroup contact may have differential effects on attitudes and beliefs, whereby intergroup contact especially reduces stereotype based prejudice (Weber and Crocker, 1983;Pettigrew and Tropp, 2006). To this extent, some studies in our meta-analysis reported that contact (Hein et al, 2011) or professional status (Krischler and Pit-ten Cate, 2019) resulted in differences in explicit attitudes and beliefs but not implicit attitudes. In contrast, found that teachers working in heterogeneous schools had less biased implicit attitudes than teachers in homogeneous settings.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, intergroup contact may have differential effects on attitudes and beliefs, whereby intergroup contact especially reduces stereotype based prejudice (Weber and Crocker, 1983;Pettigrew and Tropp, 2006). To this extent, some studies in our meta-analysis reported that contact (Hein et al, 2011) or professional status (Krischler and Pit-ten Cate, 2019) resulted in differences in explicit attitudes and beliefs but not implicit attitudes. In contrast, found that teachers working in heterogeneous schools had less biased implicit attitudes than teachers in homogeneous settings.…”
Section: Discussionmentioning
confidence: 81%
“…For two studies (Conaway and Bethune, 2015;Krischler and Pit-ten Cate, 2019), multiple dependent effect-sizes related to multiple comparisons were reported. In accordance with the guidelines of Borenstein et al (2009), these were averaged into a composite score.…”
Section: Data Preparationmentioning
confidence: 99%
“…This component is mainly assessed via questionnaires (Krischler and Pit-ten Cate, 2019) because it is compromised by beliefs (Avramidis, Bayliss and Burden, 2000). The affective component represents the evaluation of the object as negative, positive or neutral and can be assessed using implicit attitudes tests (Krischler and Pit-ten Cate, 2019). Interestingly, when considering attitudes towards ethnic minority students, mainly four dimensions are discussed as being relevant (Bakari, 2003).…”
Section: Explicit and Implicit Measuresmentioning
confidence: 99%
“…Teaching inclusively is generally "associated with providing services to ensure that all students regardless of their ability can achieve their full potential in an appropriate education setting" (O'Brien et al, 2009, p. 46). On the other hand, such an inclusive education system and teaching inclusively require particular skills, behavior, and attitudes (Darling-Hammond and Bransford, 2007;Krischler and Pit-ten Cate, 2019), as well as particular structural conditions (Booth and Ainscow, 2011). This means, for example, that teachers are required to plan their lessons with the abilities of all students in mind, that they support the learning and participation of all students with a variety of pedagogical arrangements, and that they make use of students' differences as a resource for teaching and learning (Booth and Ainscow, 2011).…”
Section: Introductionmentioning
confidence: 99%